Five Islands - (:unkn) unknown (Stephens Ltd., Trinidad, 2011)
The postcard shows some islands off the north western coast of Trinidad belonging to a group of islands called "The Five Islands" or Las Cotorras by the Spaniards and Les Perroquets by the French. This postcard is postmarked 1908.
Colour: Coloured; Style: Landscape; Other: Unbordered, Undivided
Keywords: Trinidad and Tobago; Postcards; 1908; Islands--Trinidad and Tobago; Paria, Gulf of (Venezuela and Trinidad and Tobago); Five Islands, The